2005
DOI: 10.1007/s11121-005-3412-5
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Income, Education, Safety Belt Use, and Fatal Motor Vehicle Crashes in California

Abstract: This paper investigates the role that acculturation, income, and education play in safety belt nonuse among Californian drivers involved in fatal Motor Vehicle Crashes (MVCs). To achieve this goal, measures of acculturation, income, and education were stochastically incorporated into the Fatality Analysis Reporting System (FARS). Using the 1990 California Tobacco Survey and U.S. Census data, we estimated the combination of zip-code-based measures that most accurately predicts an individual, language-based accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Our fi ndings confi rmed previous reports showing the causal role of alcohol on seat belt nonuse (Romano et al, 2005;Tsai et al, 2010), with alcohol impairment (BAC ≥ .08) signifi cantly associated with seat belt nonuse. Drivers ages 21-34 years were more likely to drive without wearing a seat belt than drivers of any other age.…”
Section: Descriptive Analysissupporting
confidence: 91%
“…Our fi ndings confi rmed previous reports showing the causal role of alcohol on seat belt nonuse (Romano et al, 2005;Tsai et al, 2010), with alcohol impairment (BAC ≥ .08) signifi cantly associated with seat belt nonuse. Drivers ages 21-34 years were more likely to drive without wearing a seat belt than drivers of any other age.…”
Section: Descriptive Analysissupporting
confidence: 91%
“…Among immigrants, differences in level of acculturation have been shown to influence safety belt use among Hispanics. 45 The population of states with secondary enforcement laws was very similar to that of states with primary enforcement laws, which suggests that conversion to primary laws could lead to levels of safety belt use similar to those now observed in primary law states.  RESEARCH AND PRACTICE  One notable exception is the disproportionate distribution of rural residents in our study, which may contribute in part to the lower overall rates of belt use observed in states that have secondary laws.…”
Section: Discussionmentioning
confidence: 60%
“…Whether youth had a driver's license was measured using one item, “Do you have a valid driver's license (not a driver's permit)?”. A measure of seatbelt use was also included because there is evidence that youth who use seatbelts are at lower risk for other risky behaviors (Romano, Tippetts, Blackman, & Voas, 2005; Shults, et al, 2009). This was measured using one item: “How often do you wear a seatbelt when you are riding in or driving a car?”.…”
Section: 1 Methodsmentioning
confidence: 99%